MEMBACA ULANG PERMASALAHAN MUH?ALLIL DALAM AL-BAQARAH [2]: 230 (SEBUAH ANALISIS TAFSIR MAQ??IDI AL-TA?R?R WA AL-TANW?R ) - Mufida Ulfa Mufida Ulfa (Program Studi Ilmu Al-Qur'an dan Tafsir STAIN Mandailing Natal, 2023)
The problem of mu?allil is quite an interesting problem, because in mu?allil practice there is what is known as mu?allil engineering. In responding to this, the scholars differed slightly in opinion, there were a few who allowed it, with enough permission. Seeing this, the author feels interested in examining more deeply the purpose and wisdom of the requirement of mu?allil in three divorces. To examine these goals and wisdom, the author traces through the book of commentaries al-Ta?r?r wa Tanw?r by Ibn Asyur, namely a scholar who focuses on Maq??id al-Syar?'ah. This type of research is descriptive qualitative with a focus on library research in which the object of study is the book al-Tahr?r wa al-Tanw?r by Ibn 'Asy?r using the content analysis method, namely analyzing the content of Ibn Asyur's description/interpretation in the book Tafsir al-Tahrir wa al-Tanwir The results of this study are that the goals and lessons of mu?allil are as follows, first, is a preventive measure so that husbands do not take the issue of divorce lightly. Second, so that the husband does not treat his wife arbitrarily, does not belittle her and make her a toy in her home. Third, as an 'iqab or torture for a husband who belittles his wife's rights, because the husband will feel tormented knowing that his wife, who is still loved, is slept with by another man. Fourth, as a lesson for husbands, so that they are aware of the difficulty of marrying a woman who is in another man's marriage so that it is not easy to divorce.